Ageing and Covid-19 Making Sense of a Disrupted World - Łuszczyńska, Maria; Formosa, Marvin (Social Perspectives on Ageing and Later Life, 2021)
This volume presents a range of research approaches to the exploration of ageing during a pandemic situation. One of the first collections of its kind, it offers an array of studies employing research methodologies that lend themselves to replication in similar contexts by those seeking to understand the effects of epidemics on older people. Thematically organised, it shows how to reconcile qualitative and quantitative approaches, thus rendering them complementary, bringing together studies from around the world to offer an international perspective on ageing as it relates to an unprecedented epidemiological phenomenon. As such, it will appeal to researchers in the field of gerontology, as well as sociologists of medicine and clinicians seeking to understand the disruptive effects of the recent coronavirus outbreak on later life.